Tables for the hydraulic design of pipes, sewers and channels - Barr, D. I. H. (Thomas Telford, 2006)
This is the first of two self-supporting volumes that make up the eighth edition. It provides a comprehensive range of solutions of the Colebrook-White equation. The tables are in the format established in previous editions, whilst a new setting adopts 50 gradient increments per order of magnitude change.
Previous ed.: 1998.
Keywords: Pipe -- Hydrodynamics -- Tables.; Drainage pipes -- Design -- Tables.; Pipelines -- Tables.; Sewer design -- Tables.; Channels (Hydraulic engineering) -- Tables.; elektronické knihy; electronic books